Central bankers, bureaucratic incentives, and monetary policy - Toma, Eugenia Froedge; Toma, Mark. (Dordrecht ; Boston : Kluwer Academic Publishers, 1986)
In recent years there has been a shift in the way economists analyze central banks. Studies in the past have assumed that the central bank acts in the interest of the public. More recently, economists have begun to question why central banks behave as they do. In addressing this question, these studies emphasize the institutional structure of central banks. The collection therein takes a look at the behavior of central banks by examining the constraints confronting bank members.
Includes bibliographies.
nmn 30/05/13
Loans
Keywords: Monetary policy; Banks and banking, Central; Central banking - bureaucratic incentives